The Demand Function for Industrial Exports: A Cross-Country Analysis - Sato, Kazuo (The Review of Economics and Statistics, 1977)
A country's exports are conventionally explained by its export prices relative to competitors' prices and by importing countries' real income. Except for its export prices, the demand for its exports is determined by factors beyond its control. It is thus usually assumed that the country passively responds to the multiplier effect that export demand generates in its domestic economy. This view is common both in macroeconomic theories of short-run income determination and long-run growth of an open economy. However, competition is imperfect in international trade. Apart from barriers set up artificially by importing countries, there are non-price factors in product quality, marketing, and services that make competition imperfect in international markets. Just as sellers can influence their demand curves in domestic markets by advertising, exporters can affect foreign demand through non-price competitive activities, e.g., export promotion. Moreover, imperfect availability of information gives a strong edge to well-established trading connections, which should become firmer as the exporting country expands in scale. In a dynamic world, process and product innovations are continually introduced; old goods are improved in quality and new goods come into existence. A country that leads others in initiating these innovations enjoys a dynamic comparative advantage. Thus, we can make a strong case that non-price competitiveness is significantly associated with an exporting country's growth performances. This argument suggests that domestic growth is an important determinant of the growth potential of a country's industrial exports. A fast-growing country could increase its exports more rapidly than a slow-growing country. While the former enjoys trade surpluses, the latter suffers from trade deficits. The balance of trade could be divergent rather than convergent in the process of growth. The experiences of industrial countries in the two decades preceding 1971 seem to be consistent with this interpretation. We wish to test our hypothesis and to evaluate how far it can account for differences in individual countries' export performances. This article presents such an empirical test by examining export records of major industrial countries over the 1955-1970 period through estimating a cross-country export demand function. Our investigation indicates that domestic factors were a particularly important determinant of export demand. We emphasize that the omission of these factors from the export demand function can make trade projections err and, consequently, lead to wrong policy prescriptions. We introduce export demand and supply functions in section II, examine data and variables in section III, present cross-country estimates of the export demand function in section IV, account for intercountry variations in the conventionally estimated world-income elasticity of export demand in section V, discuss a few econometric problems in section VI, and give concluding remarks in section VII.